2005
DOI: 10.1007/s10751-005-9159-3
|View full text |Cite
|
Sign up to set email alerts
|

151Eu Mössbauer Spectroscopy in La0.38Eu0.29Ca0.33MnO3

Abstract: Electrical conductivity with and without magnetic field, d.c. magnetization and 151 Eu Mössbauer studies were carried out in La 0.48 Eu 0.29 Ca 0.33 MnO 3 perovskite manganite system. An insulating ground state is found throughout the temperature range with charge ordered (CO) state emerging at T C0 õ 140 K, where as an external magnetic field of 6 T induces metalYinsulator transition at õ120 K. D.C. magnetization measurements show the antiferromagnetic (AFM) transition occurring at T N $ 48 K. The temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…As mentioned above, a smaller ionic radius rare earth ion, such as Eu, doping into the LCMO system induces local structural distortions leading to the tilting of the MnO 6 octahedra. In our previous studies we found that the metal-insulator transition temperature decreases to 130 K in the La 0.50 Eu 0.17 Ca 0.33 MnO 3 system and to 78 K in the La 0.46 Eu x0.21 Ca 0.33 MnO 3 system [20,21]. The decrease in the lattice parameters was also observed with the increase in Eu content [20,21].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As mentioned above, a smaller ionic radius rare earth ion, such as Eu, doping into the LCMO system induces local structural distortions leading to the tilting of the MnO 6 octahedra. In our previous studies we found that the metal-insulator transition temperature decreases to 130 K in the La 0.50 Eu 0.17 Ca 0.33 MnO 3 system and to 78 K in the La 0.46 Eu x0.21 Ca 0.33 MnO 3 system [20,21]. The decrease in the lattice parameters was also observed with the increase in Eu content [20,21].…”
Section: Discussionmentioning
confidence: 73%
“…Electrical transport measurements in low magnetic fields show the melting of spin polarons with the increase in the magnetic field [19]. The 151 Eu Mossbauer studies in La 0.67−x Eu x Ca 0.33 MnO 3 suggest local structural re-ordering at phase transition boundaries supporting the intricate relation between the lattice, charge and spin degrees of freedom [10,20]. In many recent studies, a resistivity minimum was observed in manganites, no matter whether polycrystalline, quality film or single crystal, which is similar to the Kondo effect [21][22][23].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The electrical transport measurements under low magnetic field of such compounds had shown melting of the spin polarons with the increase of magnetic field [16]. The 151 Eu Mössbauer studies in La 0.67−x Eu x Ca 0.33 MnO 3 suggested that the local structural reordering at phase transition boundaries supports the intricate relation between the lattice, charge and spin degree of freedom [17,18]. In a recent study, Reddy et al [19] reported that magnetic field induced transitions in La 0.42 Eu 0.25 Ca 0.33 MnO 3 manganites were due to strong competition between electron, phonon, charge and spin interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Spectroscopic studies based on neutron [10], EXAFs [11], µSR [12] reveals the role of JT phonons is vital in controlling the electrical transport. Partial replacement of La by Eu in this system is expected to reveal importance of the role of JT phonons play important role around phase transition boundaries in these materials [11,13].…”
Section: Introductionmentioning
confidence: 98%